Analisis Ketahanan Pangan Rumah Tangga Tani Padi (Studi Kasus: Desa Melati II, Kecamatan Perbaungan, Kabupaten Serdang Bedagai) - Johan Tarigan; Khairul Lubis; Foeza Saragih (Universitas Medan Area, 2020)
Food security is a form where the community has adequate food at the regional level and also each household, and is able to access food sufficiently for all family members, so they can live healthy and work proactively. This study aims to look at how much food-resistant rice farming households and see what factors affect the level of food security of rice farming households. Samples were taken by purposive method, which determines the sample taken is a household unit of rice farmers with as many as 30 samples. The method used is multiple linear regression. The variables studied were cooking oil prices, egg prices, tempe prices, chicken prices, tofu prices, granulated sugar prices, instant noodle prices, rice farming income, non-rice farming income, and the number of family members.